2014
DOI: 10.1111/iju.12491
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes attenuates urothelial modulation of detrusor contractility and spontaneous activity

Abstract: Abbreviations & AcronymsObjectives: To investigate the effect of diabetes on urothelial modulation of bladder contractility. Methods: Bladder strips (urothelium intact or denuded) were prepared from 8-week-old streptozotocin-induced diabetic (n = 19) and non-diabetic control rats (n = 10). The effect of modulators of MaxiK (iberiotoxin and tetraethylammonium) and Kv7 (XE991 and retigabine) potassium channel activity were investigated for their effects on both carbachol-induced force generation and spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Thus, if diabetes has differential effects on MaxiK activity in urothelium and detrusor, then diabetes-induced changes in the effect of IBTX on UBSM contractility maybe primarily mediated through the urothelium. Indeed, we and others [ 5 , 35 ] have published that the presence of the urothelium on UBSM strips from non-diabetic animals increases sensitivity of carbachol-induced contractility to IBTX, although this effect is attenuated with diabetes. The data presented here further establishes an important role for the urothelium in regulating bladder physiology, urothelial MaxiK activity not only regulates mucosal, but also detrusor activity.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, if diabetes has differential effects on MaxiK activity in urothelium and detrusor, then diabetes-induced changes in the effect of IBTX on UBSM contractility maybe primarily mediated through the urothelium. Indeed, we and others [ 5 , 35 ] have published that the presence of the urothelium on UBSM strips from non-diabetic animals increases sensitivity of carbachol-induced contractility to IBTX, although this effect is attenuated with diabetes. The data presented here further establishes an important role for the urothelium in regulating bladder physiology, urothelial MaxiK activity not only regulates mucosal, but also detrusor activity.…”
Section: Discussionmentioning
confidence: 90%
“…However the surgery to insert the catheter was performed 4 days prior to the infusion of IBTX which would allow for healing of bladder tissue at the site of catheter entry. During the infusion of IBTX the bladder is not over-distended and several studies suggest that filling the bladder to capacity does not affect bladder permeability [ 5 7 ]. In addition, the surgery to insert the infusion catheter into the bladder lumen, or over-distention of the bladder during infusion, may result in the loss of barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rat is the next most common animal species in which DSM K V 7 channels have been studied, but only three publications are currently available (Argentieri and Sheldon, 2006;Rode et al, 2010;Wang et al, 2014) and a single report on pig DSM (Svalo et al, 2013). In rat DSM, retigabine and ML213 effectively inhibited DSM spontaneous phasic, 20 mM KCl-induced phasic, or carbachol-potentiated phasic contractions (Argentieri and Sheldon, 2006;Rode et al, 2010;Wang et al, 2014). The elevation of extracellular K + , which results in a reduction of the driving force for K + , caused attenuation in retigabine-induced relaxation (Argentieri and Sheldon, 2006).…”
Section: Studies Of Dsm Contractility In Experimental Animal Modelsmentioning
confidence: 99%
“…Dahlin et al [ 60 ] reported that thinly myelinated fibers were more susceptible to oxygen deprivation under ischemic conditions than thicker ones, whereas unmyelinated fibers were resistant to ischemic induction. Furthermore, attenuation of urothelial sensitivity to modulators of potassium channel activity has been observed in diabetic bladders [ 61 ], which may cause afferent sensory dysfunction [ 33 62 63 64 ], as well as contribute to contractile force and spontaneous activity of the detrusor smooth muscle [ 61 ]. Mohammed et al [ 65 66 ] reported that aged rats showed significant decreases in the expression of calcitonin gene-related peptide (CGRP) and substance P on the lumbosacral dorsal root ganglion neurons and in the density of pituitary adenylate cyclase-activating polypeptide innervation on the subepithelial plexus and the muscle layer of the bladder, whereas CGRP and substance P innervation on the muscle layer were slightly reduced.…”
Section: Factors Contributing To Underactive Bladdermentioning
confidence: 99%